Fish Coolbox using Coconut Fiber (Cocos nucifera) and Baggage (Saccharum sp) Insulated - Thahir, Muhammad Agam; Nurlaili, Nurlaili; Khairi, Ikhsanul (Jurnal Perikanan dan Kelautan, 2023)
The quality of the catch can be seen from the fish storage container used to maintain its temperature. An insulated storage area can maintain ice resistance during the operation of fishing gear, as well as during the transportation of the catch to the fish landing site. Generally, fishermen use fish storage containers made of fiber with insulation in the form of polyurethane. Some fish storage containers are made from polystyrene-insulated styrofoam. This research aims to determine how optimal cooling is using coconut fiber and sugar cane bagasse insulation. The method used in this research was an experimental method using a Completely Randomized Design (CRD) with one control (Styrofoam cooler box), two treatments (Coconut fiber insulated cooler box and sugarcane bagasse), and three repetitions. The dimensions of the coolbox are the same as those on the market, namely 42 cm x 26 cm x 23 cm and a thickness of 2 cm. The lowest temperature of the coolbox made from coconut fiber insulation, 17.7 °C, was reached after the 70th minute. The bagasse was only able to reach the lowest temperature of 19.4°C, achieved in the 60th minute. Temperature stability in the coconut fiber coolbox reached 2 hours 10 minutes (130 minutes) from 80-200 minutes, while the bagasse coolbox reached 3 hours 40 minutes (220 minutes) from 70-280 minutes.